(untitled) (Research, Society and Development, 2020)
The "origin of life" and "we are alone in the Universe" have always been unknown to the scientific community and much of the population. Astrobiology is a recent area that seeks to understand how life originated and evolved during these billions of years of the cosmos’s existence. This article aims to clarify questions related to the origin of life and possible routes about the possibility of living and finding life outside the Earth, without any connection with religious dogmas. For this, the methodology used was to perform a bibliographical review on the central theme through astrobiology. This will cover topics such as microorganisms called extremophiles, conditions for a planet to be considered in a habitable region, possibilities for life to exist on Mars, and briefly address issues related to the possibility of colonization of our red planetary neighbor. With the obtained results it was concluded that Astrobiology proves to be a convergent area to the interests for the search for answers about the origin of Life and it is hoped that it can be used as a basis for future teaching and scientific dissemination work.